Nano-design of quantum dot-based photocatalysts for hydrogen generation using advanced surface molecular chemistry. Issue 2 (20th November 2014) - Yu, Weili; Noureldine, Dalal; Isimjan, Tayirjan; Lin, Bin; Del Gobbo, Silvano; Abulikemu, Mutalifu; Hedhili, Mohamed Nejib; Anjum, Dalaver H.; Takanabe, Kazuhiro
Abstract : A molecular linking strategy is demonstrated to achieve efficient electron transfer and hydrogen evolution using a (CdSe–ZnS)–TiO2 –(Au–Pt) photocatalyst. Abstract : Efficient photocatalytic hydrogen generation in a suspension system requires a sophisticated nano-device that combines a photon absorber with effective redox catalysts. This study demonstrates an innovative molecular linking strategy for fabricating photocatalytic materials that allow effective charge separation of excited carriers, followed by efficient hydrogen evolution. The method for the sequential replacement of ligands with appropriate molecules developed in this study tethers both quantum dots (QDs), as photosensitizers, and metal nanoparticles, as hydrogen evolution catalysts, to TiO2 surfaces in a controlled manner at the nano-level. Combining hydrophobic and hydrophilic interactions on the surface, CdSe–ZnS core–shell QDs and an Au–Pt alloy were attached to TiO2 without overlapping during the synthesis. The resultant nano-photocatalysts achieved substantially high-performance visible-light-driven photocatalysis for hydrogen evolution. All syntheses were conducted at room temperature and in ambient air, providing a promising route for fabricating visible-light-responsive photocatalysts.